Recharge PSYCH: a study on rechargeable implantable pulse generators in deep brain stimulation for psychiatric disorders - Jakobs, Martin; Hajiabadi, Mohammad Mehdi; Aguirre-Padilla, David Hernán; Giaccobe, Peter; Unterberg, Andreas; Lozano, Andres M. (World neurosurgery, 2023)
Background - Rechargeable implantable pulse generators (r-IPGs) for deep brain stimulation (DBS) promise longer battery life and fewer replacement surgeries versus non-rechargeable systems. Long-term data on the effects of recharging in patients who received DBS for psychiatric indications is limited. The Recharge PSYCH trial is the first study that included DBS patients with psychiatric disorders treated with different r-IPG models. - Methods - Standardized questionnaires were sent to all psychiatric DBS patients with an r-IPG implanted at the time of the study. The primary endpoint was convenience of recharging. Secondary endpoints were rate of user confidence and rate of usage-related complications, as well as charge burden (defined as minutes per week needed to recharge). - Results - Data sets of n = 21 patients were eligible for data analysis. At the time of the survey patients were implanted with the r-IPG for a mean 31.8 ± 22.4 months. Prior to being implanted with an r-IPG, patients had undergone a median of 3 IPG replacements. The overall convenience of the charging process was rated as "easy" with a median of 8.0 out of 10.0 points. 33.3% of patients experienced situations in which the device could not be successfully recharged. In 38.1% of patients, therapy with the r-IPG was interrupted unintentionally. The average charge burden was 286 ± 22.4 minutes per week. - Conclusions - Patients with psychiatric disorders rated the recharging process as “easy”, but with a significantly higher charge burden and usage-related complication rates compared to published data on movement disorder DBS patients.